PERAN MAJELIS TAKLIM DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN - Sutarjo Sutarjo (Universitas Singaperbangsa Karawang, 2021)
Majelis taklim is one of the non-formal educational institutions that has a major contribution in developing and fostering Islamic religious knowledge. Majelis taklim in Indonesia have developed rapidly in society, ranging from a few members to thousands of members. One of the taklim assemblies that took part in Cintaasih Village, Pangkalan District, Karawang Regency, namely the Sunday morning recitation which is managed by the Bakan Pedes Darussalam Islamic Boarding School. This study aims to describe the role of the Sunday morning recitation in Cintaasih Village in increasing religious understanding. This study uses a qualitative approach because the data obtained is processed and explained in the author's study. In obtaining data, the author uses the method of observation, interviews and documentation. Sources of data in this study include primary data sources, namely the results of interviews with caregivers, administrators and several Sunday morning recitation congregations in Cintaasih Village, as well as secondary data sources derived from documentation of activities. As for the findings of the role of the Sunday morning recitation in Cintaasih Village in increasing religious understanding, namely: (1) Fostering the faith of the congregation, after attending this Sunday morning recitation the congregation felt an increase in faith. (2) Fostering families in realizing the sakinah family through bahsul masail activities on Sunday legi. (3) Empowerment of the duafa by holding orphanage assistance activities every Muharram month. (4) Increasing the household economy with the large number of congregations participating in the Koran while selling. (5) As a place to study religious knowledge, so as to increase religious understanding. (6) Fostering harmony among the people with friendship